2010
DOI: 10.5194/acp-10-9593-2010
|View full text |Cite
|
Sign up to set email alerts
|

Source apportionment of PM<sub>2.5</sub> in Cork Harbour, Ireland using a combination of single particle mass spectrometry and quantitative semi-continuous measurements

Abstract: Abstract. An aerosol time-of-flight mass spectrometer (ATOFMS) was deployed for the measurement of the size resolved chemical composition of single particles at a site in Cork Harbour, Ireland for three weeks in August 2008. The ATOFMS was co-located with a suite of semi-continuous instrumentation for the measurement of particle number, elemental carbon (EC), organic carbon (OC), sulfate and particulate matter smaller than 2.5 µm in diameter (PM 2.5 ). The temporality of the ambient ATOFMS particle classes was… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
78
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(97 citation statements)
references
References 100 publications
5
78
3
Order By: Relevance
“…Dicarboxylic acids represent 4-15% of the total aerosol mass of atmospheric aerosol particles from continental and marine samples (24) and are formed from biomass burning, fossil fuel combustion, cooking, automobile exhaust, and atmospheric reactions of biogenic and anthropogenic VOCs (25). Field measurements deploying a single particle spectrometer, Aerosol Time of Flight Mass Spectrometer (ATOFMS), confirmed the presence of internally mixed particles containing organic carbon, ammonium, and nitrate (26).…”
Section: Atmospheric Chemistry | Photoinduced Processesmentioning
confidence: 99%
“…Dicarboxylic acids represent 4-15% of the total aerosol mass of atmospheric aerosol particles from continental and marine samples (24) and are formed from biomass burning, fossil fuel combustion, cooking, automobile exhaust, and atmospheric reactions of biogenic and anthropogenic VOCs (25). Field measurements deploying a single particle spectrometer, Aerosol Time of Flight Mass Spectrometer (ATOFMS), confirmed the presence of internally mixed particles containing organic carbon, ammonium, and nitrate (26).…”
Section: Atmospheric Chemistry | Photoinduced Processesmentioning
confidence: 99%
“…The combination of ATOFMS and hygroscopicity tandem differential mobility analyser (HTDMA) data has shown that sea salt and particles containing amines and nitrate are hydrophilic, while the more organic carbon (OC) particles contain the more hydrophobic they are (Herich et al, 2009;Wang et al, 2014). Fresh particles can be distinguished from aged ones by the presence of secondary inorganic species such as nitrate, sulfate and ammonium (Cahill et al, 2012;Healy et al, 2010;Liu et al, 2003;, which is also helpful in differentiating particles from local and transported sources (Healy et al, 2012). Single particle chemical speciation is therefore a useful tool for examining the effect aerosols have on air quality and climate, and is complementary to characterising particle optical and physical properties (Moffet and Prather, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Single particle mass spectrometers, such as the aerosol time-of-flight mass spectrometer (ATOFMS), have proven valuable in identifying and characterising a wide variety of particle sources: sea salt, mineral dust, vehicle exhaust, tyre wear, solid fuel combustion (coal, peat and wood), shipping and various industrial emissions Bhave et al, 2001Bhave et al, , 2002Dall'Osto et al, 2014;Giorio et al, 2012;Harrison et al, 2012;Healy et al, 2009Healy et al, , 2010Healy et al, , 2012Liu et al, 2003;Spencer et al, 2008;Tao et al, 2011). Mixing state information -both internal and external -provided by mass spectrometers has been used to determine the type of atmospheric processing particles have undergone (Gard et al, 1998), as well as their acidity and hygroscopicity (Denkenberger et al, 2007;Healy et al, 2014), properties which affect their ability to act as CCN (cloud condensation nuclei; Furutani et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Though, the primary PM 2.5 (particulate matters with aerodynamic diameter less than or equal to 2.5 μm) emitted from ships only account for a low proportion (1.5% in Cork Harbour e.g.) (Healy et al, 2010) of total PM 2.5 in ambient air compared with other sources, 3-8% of deaths associated with PM 2.5 emission globally were linked to shipping emission (EPA, 2009). Due to its complex mechanism and high absorption capacity for toxic chemicals, such as polycyclic aromatic hydrocarbons, PM exhausted by ships could cause more serious human health risk than by direct emissions (EPA, 2009).…”
Section: Introductionmentioning
confidence: 99%